Effects of fresh frozen plasma infusions on coagulation screening tests in neonates. Issue 12 (December 1982) - Johnson, C A; Snyder, M S; Weaver, R L
Abstract : Infusion of fresh frozen plasma to 23 immature infants with respiratory distress syndrome produced full correction of prothrombin time and activated partial thromboplastin time in only 7. Improvements in coagulation studies failed to correlate with gestational age or with the initial degree of coagulation abnormality.